Innovations in diagnostics and treatment to fight the HIV epidemic (Research, Society and Development, 2022)
HIV is the human immunodeficiency virus, which causes a sexually transmitted infection (STI) that still affects a large part of the population, despite being an infection that has been known for a long time. The objective of the present work is to gather information related to innovations in diagnosis and treatment of this infection, in which its growth rate is decreasing more and more, but it is still a very worrying public health issue in several countries. We used the qualitative research methodology with a narrative and descriptive review based on scientific articles published on platforms such as PubMed, Scielo and data collected from the Ministry of Health, World Health Organization and UNAIDS. Unfortunately, diagnosis is not always quick due to various factors, such as difficult access to health services, or even information, however a much talked about innovation lately was the HIV self-test, where people can self-examine themselves through a rapid test, by oral fluid or blood, performing the exam in your own home. The self-test is very easy to be performed, in addition to the fact that it is offered free of charge by the SUS, and only if it is positive does the person need to look for a basic health unit or a hospital to perform the confirmatory test (ELISA or Western Blot) and perform the follow-up treatment. Treatment is usually done with a mixture of medications, known as antiretrovirals, but a new treatment is being researched and proposes many improvements in this area, which is gene therapy, with CRISPR/CAS9 added to the use of LASER ART, which consists of slow and prolonged release antiretroviral nanoparticles, increasing the effectiveness of drugs and decreasing off-target toxicity. We conclude that there are several factors involved in these innovations presented, with the self-test it is possible to reach populations that were not reached before and create larger campaigns to bring necessary information about the importance of the diagnosis as soon as possible and of carrying out the test to follow the evolution. As for gene therapy with CRISPR/CAS9 and LASER ART, results that were not achieved before, such as the cure for HIV, when the two techniques combined it was possible to eradicate the virus from the tested mice, however, limits must be drawn to the technique, to not infringe on the ethical and moral issues that it may offer.